Development of mind mapping and learning objectives flow (ATP) based on Kikuduko for mathematics teachers in the MGMP of junior high schools in Kayuagung city - Indaryanti; Meryansumayeka; Scristia; Elika Kurniadi; Zuli Nuraeni (LP2M Universitas Islam Negeri Mataram, 2023)
[Bahasa]: Kurikulum merdeka menuntut para guru memahami komponen atau istilah yang ada di dalamnya, salah satunya yaitu ATP atau Alur Tujuan Pembelajaran. Untuk dapat merumuskan ATP, guru juga perlu penguasaan dalam menyusun mind mapping atau peta konsep matematika yang perlu dipelajari oleh siswa. Guru perlu memahami ATP sebagai panduan yang esensial dalam merancang pembelajaran yang efektif dan relevan. Tujuan utama kegiatan ini adalah memberikan pelatihan dan pendampingan kepada guru dalam penyusunan mind mapping dan ATP berbasis Kikuduko dalam upaya meningkatkan kompetensi para guru. Metode yang digunakan adalah presentasi, workshop, diskusi dan pendampingan. Kegiatan dilaksanakan secara daring dan diikuti 21 orang guru SMP dari wilayah Kota Kayuagung. Hasil dari kegiatan pelatihan dan pendampingan penyusunan mind mapping dan ATP berbasis KIkuduko ini adalah peserta pelatihan sudah mampu menyusun mind mapping dan ATP berbasis KIkuduko. Hasil analisis angket respon kepuasan aspek pendampingan yang dapat membantu peserta menyusun mindmapping dan ATP sebesar 93.75%, aspek kedua terkait pengetahuan peserta tentang mindmapping dan ATP sebesar 94.375%, aspek ketiga tentang kepuasan peserta terhadap materi yang dikaji dan pendampingan yang diberikan sebesar 95%, dan aspek keempat mengenai keterampilan peserta dalam menyusun mindmapping dan alur tujuan mendapat respon dari peserta sebesar 88.75%. Kegiatan pengabdian kepada masyarakat ini sangat efektif untuk membantu guru dalam memahami Capaian Pembelajaran dan menyusun Tujuan Pembelajaran dan Alur Tujuan Pembelajaran, serta mengenalkan guru pada mindmapping untuk memudahkan guru dalam menyusun ATP. Kata kunci: mind mapping, Alur Tujuan Pembelajaran (ATP), Kikuduko [English]: “Kurikulum Merdeka” requires teachers to understand the components or terms contained in it, one of which is ATP or Learning Objectives Flow. To be able to compile ATP, teachers also need to master compiling mind maps or maps of mathematical concepts that students need to learn. Teachers need to understand ATP as an essential guide in designing effective and relevant learning. The main objective of this activity is to provide training and assistance to teachers in preparing Kikuduko-based mind maps and ATPs in an effort to increase the competence of teachers. The methods used are presentations, workshops, discussions and mentoring. The activity was carried out boldly and was attended by 21 junior high school teachers from the Kayuagung City area. The results of the training and assistance activities in preparing KIkuduko-based mind maps and ATPs are that the training participants are able to prepare KIkuduko-based mind maps and ATPs. The results of the response questionnaire analysis of satisfaction with aspects of mentoring that can help participants prepare mindmapping and ATP is 93.75%, the second aspect is related to participants' knowledge about mindmapping and ATP is 94.375%, the third aspect is regarding participant satisfaction with the material studied and the assistance provided is 95%, and The fourth aspect regarding participants' skills in compiling mindmapping and goal flow received a response from participants of 88.75%. This community service activity is very effective in helping teachers understand Learning Achievements and compiling Learning Objectives and Learning Goal Flow, as well as introducing teachers to mindmapping to make it easier for teachers to prepare ATP. Keywords: mind mapping, Learning Objectives Flow, KIKuDuKo